Moral Autonomy and Unconditional Submission to God: - Colin P. Ruloff (TheoLogica)
A number of prominent commentators construe the concept of worship in such a way that it commits the worshipper to unconditional submission to God. One might think, however, that construing worship in this way implies that the worshipper’s moral autonomy will be undermined. In this paper I respond to and reject a recent argument by Frederick Choo that attempts to show that it’s false that unconditional submission to God undermines the worshipper’s moral autonomy.